In response to aggression : methods of control and prosocial alternatives - Goldstein, Arnold P. (Pergamon general psychology series, 1981)
In Response to Aggression: Methods of Control and Prosocial Alternatives describes and evaluates comprehensively what has been done in response to aggression, with emphasis on aggression controls and alternatives. The book is organized into four major parts. These parts deal with aggression controls and alternatives specific for individual, small group, community, and societal levels of intervention. The book will lead to enhanced utilization of methods for aggression controls and alternatives, and hence to widespread prosocial and constructive behaviors in response to aggression.